The use of antibiotics in the early stage of acute exacerbation of chronic obstructive pulmonary disease in patients without obvious signs of infection: a multicenter, randomized, parallel-controlled study - Zhou, Ling; Deng, Yan; Liu, Kui; Liu, Huiguo; Liu, Wei (Frontiers in Pharmacology, 2024)
Purpose: To clarify the impact of antibiotic treatment on the short-term and long-term prognosis of AECOPD patients without obvious signs of infection. Methods The impact of the two treatment methods on the prognosis of patients was compared at 30, 90, 180, and 360 days after discharge. A multicenter, randomized, parallel controlled clinical trial was conducted in a department of respiratory and critical care medicine in Central China. All patients med the inclusion criteria for AECOPD, and the patients were randomly assigned to the antibiotic group or the nonantibiotic group at a 1:1 ratio. Results: There were 406 patients in the antibiotic group and 410 patients in the nonantibiotic group. During the short-term and long-term follow-up, the acute exacerbation frequency, intensive care unit (ICU) treatment rate, mortality, and mMRC and CAT scores were not significantly different between the two groups (P > 0.05). The 30-day readmission rate was significantly lower in the antibiotic group than in the nonantibiotic group (P < 0.05). The time from discharge to the first acute exacerbation was not significantly different between the two groups (P > 0.05). The length of the first hospital stay after discharge was significantly lower in the antibiotic group (5.84 days) than in the nonantibiotic group (6.75 days) (P < 0.05). At the 30-day follow-up, the acute exacerbation frequency, age, C-reactive protein (CRP) level, and sputum viscosity were significantly greater in the nonantibiotic group than those in the antibiotic group (P < 0.05). In addition, according to the receiver operating characteristic (ROC) analysis, the frequency of acute exacerbations at the 30-day follow-up was significantly greater in COPD patients aged > 62.5 years, with a CRP level >12.56 mg/L or with a sputum viscosity >III in the nonantibiotic group than in those in the antibiotic group, suggesting that the short-term prognosis was poor. Conclusions: Patients who are > 62.5 years of age, have a CRP concentration >12.56 mg/L or have a sputum viscosity >III without obvious signs of infection should be treated with antibiotics to improve their short-term prognosis.